Design for Distributed Moroccan Hospital Pharmacy Information Environment with Service Oriented Architecture - Hajar Omrana; Safae Nassiri; Fatima-Zahra Belouadha; Ounsa Roudi?s (IJID (International Journal on Informatics for Development), 2012)
In the last five years, Moroccan e-health system has focused on improving the quality of patient care services by making use of advanced Information and Communications Technologies (ICT) solutions. In actual fact, achieving runtime and efficient information sharing, through large-scale distributed environments such as e-health system, is not a trivial task. It seems to present many issues due to the heterogeneity and complex nature of data resources. This concerns, in particular, Moroccan Hospital Pharmacy Information System (HPIS) which needs to interact with several disparate medical information systems. Service Oriented Architecture (SOA) offers solution that is both flexible and practical to effectively address the problem of interoperability of e-health systems. In this paper, we discuss the limits and challenges of the current Moroccan information system intended for hospital pharmacy. We therefore propose a global Web services-based e-health architecture for integrating different heterogeneous blocks and various data resources of this system. We also present a solution to secure Web services communication using WS-SecurityPolicy.